Can land value uplift deliver affordable housing? Experiences from England. Issue 1 (8th May 2018) - Wyatt, Peter
Abstract : Purpose: The theoretical case for land value capture is well-known, but the effectiveness of affordable housing delivery as a capture mechanism is not so well-documented. Building on the earlier theoretical and empirical work ofWhitehead (1991, 2007) andCrook and Whitehead (2002 ), the purpose of this paper is to consider the provision of affordable housing from a land value capture viewpoint, focusing on the process by which the amount of affordable housing is determined between landowners/developers on the one hand and local planning authorities on the other. Design/methodology/approach: The paper adopts a mixed-mode approach for the data collection. Two surveys of local planning authorities were undertaken, together with a series of case study interviews. Findings: The paper evaluates whether land value capture has been an effective mechanism for delivering affordable housing by focusing on three principal areas: first, the political agenda in relation to land value capture and the supply of affordable housing; second, the nature and motivation of the stakeholders involved in affordable housing decision-making; and third, the use of economic models as decision tools for determining the amount and type of affordable housing are negotiated. Originality/value: The research provides some insight into the effectiveness of local authority affordable housing targets as a means of capturing the uplift in land value that results from the grant of planning permission.